2012
DOI: 10.1186/1471-2474-13-200
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ views about treatment with combination therapy for Rheumatoid Arthritis: a comparative qualitative study

Abstract: BackgroundCombinations of disease-modifying anti-rheumatic drugs (DMARDs) are increasingly used to control active rheumatoid arthritis (RA); however there is little information about patients’ perspectives, their expectations, concerns and experiences of this intensive treatment.MethodWe interviewed a quota sample of 18 patients from a single tertiary outpatient clinic, stratified by gender, ethnicity and age, based on the outpatient clinic population. Patients with early RA (<2 years) received combined conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…On the contrary, it has been reported that combination therapy with MTX is usually well accepted by RA patients,18,21,22 and thus our results suggesting a preference for monotherapy may seem contradictory. Previous studies did not assess combination therapy within the framework of other relevant (second-line) DMARD attributes though.…”
Section: Discussioncontrasting
confidence: 87%
“…On the contrary, it has been reported that combination therapy with MTX is usually well accepted by RA patients,18,21,22 and thus our results suggesting a preference for monotherapy may seem contradictory. Previous studies did not assess combination therapy within the framework of other relevant (second-line) DMARD attributes though.…”
Section: Discussioncontrasting
confidence: 87%
“…Patients’ perceptions concerning the desired therapeutic outcome influence both attitudes and behaviors toward medicine 32,33. Concerns about potential harm from side effects, long-term use and/or dependency are common 10.…”
Section: Discussionmentioning
confidence: 99%
“…Practical difficulties with the long-term use of medicines have been documented as burdensome,3739 while the burden of managing medicine routines has been reported as demanding of both time and resources 8,18. There is also evidence that many patients manipulate their medicine regimens, especially when they experience unbearable burden, perceive their medicines as inappropriate or are dissatisfied with their medicine 33,4042. Conversely, regimens which are inconvenient may lead to perceived lack of control or autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, some participants considered reluctance and/or negative attitude towards use of medications, diet, exercise, and social interactions as predisposing factors for failing to adopt SMB. In studies by Dixon and Bansback (27), Lempp et al (28), patients had negative attitudes towards medications and their side-effects. Furthermore, in this study, some of the female participants expressed negative attitudes towards using canes or neck orthotics and supports due to the fact that their devices were not accepted by their partner and perceived as a sign of disability.…”
Section: Discussionmentioning
confidence: 99%